2008
DOI: 10.1111/j.1439-0264.2008.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of the Tricuspid Valve in Dogs

Abstract: An anatomical study of the tricuspid valve was performed in the hearts of 45 dogs using a method of dissection which preserves the integrity of the valve. Morphometrical criteria such as the width of the cusp base and larger depth of cusp and morphological criteria such as the number of tendinous cords, the perimeter of the fibrous ring and the properties of the papillary muscle were adopted for the characterization of a cusp. The tricuspid valve was not consistent with three cusps, but it was observed to pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 6 publications
1
12
1
Order By: Relevance
“…They also indicated presence of the "supernumerary", "accessory" or "commissural" cusps, along with the three cusps. The number of these "supernumerary", "accessory" or "commissural" cusps may be 1-2 [2,21,64], 1-3 [66], or 1-4 [29,36,43,60]. In this study, all of the hearts had three eminent cusps and one or two commissural (accessory) cusps.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…They also indicated presence of the "supernumerary", "accessory" or "commissural" cusps, along with the three cusps. The number of these "supernumerary", "accessory" or "commissural" cusps may be 1-2 [2,21,64], 1-3 [66], or 1-4 [29,36,43,60]. In this study, all of the hearts had three eminent cusps and one or two commissural (accessory) cusps.…”
Section: Discussionmentioning
confidence: 64%
“…The septal and posterior papillary muscles were shown to be located on the septal wall, while the anterior papillary muscle on the parietal wall [3,13,15,21,29]. Again, the anterior papillary muscle in the Guinea pig is located either between the junction of the two walls on the apical region [5] or on the septal wall as is the case in mouse [26], rabbit [5] and dogs [2,58]. In our study, the septal papillary muscle was found on the septal wall, while the anterior papillary muscle was located on the parietal wall, which is in resemblance to some reports [3,13,15,21] but contrary to others [2,5,26,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the tricuspid valve (TV) is composed of three leaflets while in dogs, it has been reported that the TV may consist of two to five leaflets (Alves et al, 2008). The majority of dogs have a TV that is composed of three or four leaflets.…”
Section: Embryology Anatomy and Physiology Of Atrioventricular Valvesmentioning
confidence: 99%
“…Exceptionally, a fifth leaflet may be present between the septal and angular leaflet. In these cases, the septal and mural leaflets are less prominent (Alves et al, 2008). The leaflets are anchored by the chordae tendineae to the papillary muscles and papillae.…”
Section: Embryology Anatomy and Physiology Of Atrioventricular Valvesmentioning
confidence: 99%